Providing a Model of Diversity and Inclusion in Human Resource Management with a Focus on Digital Transformation Tools - Adabi, Mersedeh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The aim of this research is to provide a model of diversity and inclusion in human resource management with a focus on digital transformation tools.Methodology: The study is applied in terms of purpose and exploratory in nature. The participants in the research included 14 experts and human resource managers, selected through purposive sampling of the judgmental type. To identify the components, thematic analysis was used. For data processing, the structural equation modeling method was applied using MICMAC software.Findings: Based on the results, 15 criteria (transparency in decision-making, personalization of employee experience, digital key performance indicators, digital platforms, digital feedback, impartial digital assessments, digital culture building, big data analysis, artificial intelligence, digital communication tools, standardization of recruitment and hiring processes, digital performance management systems, digital learning platforms, diversity and inclusion awareness and training programs, equal access to digital resources, and digital support systems) were categorized into six levels.Conclusion: This study emphasizes the importance of integrating digital transformation tools in human resource management to promote diversity and inclusion. The proposed model highlights key factors such as transparency, AI, and digital learning platforms, offering valuable insights for organizations seeking to create more inclusive and equitable work environments.